Exceptional Hydrogen Diffusion Rate over Ru Nanoparticle‐Doped Polar MgO(111) Surface. Issue 3 (22nd January 2023) - Yoskamtorn, Tatchamapan; Mo, Jiaying; Chen, Lu; Wu, Simson; Mukhopadhyay, Sanghamitra; Hawkins, Alex; Wu, Xin‐Ping; Tsang, Shik Chi Edman
Abstract: Hydrogen (H) conductivity on oxide‐based materials is crucially important in fuel cells and related catalysis. Here, this work measures the diffusion rate of H generated from Ru nanoparticles loaded on polar MgO(111) facet particles under H2 at elevated temperatures without moisture and compares it to conventional nonpolar MgO(110) for the first time by in situ quasielastic neutron scattering (QENS). The QENS reveals an exceptional diffusion rate on the polar facet via a proton (H + ) hopping mechanism, which is an order of magnitude superior to that of typical H + ‐conducting oxides. This work attributes this to the unique atomic arrangement of alternate layers of Mg cations and O anions of the polar MgO(111) where the strong electrostatic field of terminal oxygen anions facilitates protonic migration with a lower degree of local covalency. Abstract : Hydrogen mobility on oxide‐based materials is critical for fuel cells and related catalytic systems. Herein, highly diffusive hydrogen over the Ru‐supported MgO(111) surface via a proton hopping mechanism is discovered by using in‐situ quasielastic neutron scattering. This is attributed to the strong electrostatic field of terminal oxygen anions in the polar MgO(111), which allows for less‐localized covalency for the proton migration.